Prevalence and factors associated with sexual dysfunction in climacteric women - Martins, Marília; Casali Bandeira, Vanessa Adelina; Meggiolaro Gewehr, Daiana; Moraes Berlez, Evelise (O Mundo da Saúde, 2018)
The present study aimed to verify the prevalence of sexual dysfunction in climacteric women and associated factors. This study had a cross-sectional and analytical design with women in the age group of 35 to 65 years, located in the Family Health Strategy units of the city of Ijuí, RS. The sociodemographic data and the health conditions were collected at home. Later in a urofunctional consultation they answered the questionnaire "The Female Sexual Function Index (FSFI)" and provided information regarding their menstrual cycle and urinary continence. Of the 71 participants, 59.15% had sexual dysfunction. Among the risk factors for dysfunction the low level of education, aged over 50 years, non-reproductive period and occurrence of at least one vaginal delivery were observed. Among the total number of FSFI domains, the mean number of women with sexual dysfunction was 21.64±3.52 and the women with no dysfunction were 29.77±2.08. When discriminating the groups with and without dysfunction, the highest averages were in the pain and lubrification domains, respectively. These findings reinforce the importance of knowing the possible risk factors for dysfunction and the need to address this clinical condition in order to prevent it and ensure sexual health during the aging process.